New formalisms and literary theory (Palgrave Macmillan, 2013)
"New Formalisms and Literary Theory" examines the political motivations of a return to formalism. Together with our contributors, we want to propose and challenge the conception of New Formalism as an extension of contextual readings and as a 'mere' return to aesthetic readings. The essays gathered here encourage reflection upon New Formalism's points of intersection with other theoretical approaches and demand a reinstatement of form as the critic's central focus, form, that is, as it reflects a culture's creative imagination and historicizes itself within and against a politically charged background.